Frontline over ivory tower: key competencies in community-based curricula - Millar, Adam; Malcolm, Janine; Cheng, Alice; Fine, Rebecca; Wong, Rene (Revue canadienne de l'éducation médicale, 2015)
Background: The Royal College of Physicians and Surgeons of Canada mandates that community experiences be incorporated into medicine-based specialties. Presently there is wide variability in community endocrine experiences across Canadian training programs. This is complicated by the paucity of literature providing guidance on what constitutes a ‘community’ rotation. Method: A modified Delphi technique was used to determine the CanMEDS competencies best taught in a community endocrinology curriculum. The Delphi technique is a qualitative-research method that uses a series of questionnaires sent to a group of experts with controlled feedback provided by the researchers after each survey round. The experts in this study included endocrinology program directors, community endocrinologists, endocrinology residents and recent endocrinology graduates. Results: Thirty four out of 44 competencies rated by the panel were deemed suitable for a community curriculum. The experts considered the “Manager” role best taught in the community, while they considered the community least suitable to learn the “Medical Expert” competency. Conclusions: To our knowledge, this is the first time the content of a community-based subspecialty curriculum was determined using the Delphi process in Canada. These findings suggest that community settings have potential to fill in gaps in residency training in regards to the CanMEDS Manager role. The results will aid program directors in designing competency-based community endocrinology rotations and competency-based community rotations in other medical subspecialty programs.